Encounters in video art in Latin America - Shtromberg, Elena; Phillips, Glenn, 1974- (Issues & debates., 2023)
"With engaging essays and insightful interviews, this volume examines how artists have experimented with the medium of video across different regions of Latin America since the 1960s"--